2020
DOI: 10.1097/cm9.0000000000000818
|View full text |Cite
|
Sign up to set email alerts
|

Use of a compact high-definition two-dimensional exoscope in surgical treatment of large vestibular schwannoma

Abstract: Background: Extra-corporeal video telescope operating monitor system provides a necessary instrument to perform high-precision neurosurgical procedures that could substitute or supplement the traditional surgical microscope. The present study was designed to evaluate a compact high-definition two-dimensional exoscope system for assisting in surgical removal of large vestibular schwannoma (VS), as an alternative to a binocular surgical microscope. Methods: Patients with Koos grade 3 and grade 4 VS undergoing su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Chen et al 17 published a similar series comparing a two-dimensional exoscope system with the operative microscope for resection of VS. They documented a reduction of blood loss in exoscope surgeries and similar clinical and radiological results compared with microscope use.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al 17 published a similar series comparing a two-dimensional exoscope system with the operative microscope for resection of VS. They documented a reduction of blood loss in exoscope surgeries and similar clinical and radiological results compared with microscope use.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies point out, in particular, an increase in the average duration of neurosurgical intervention with respect to the same intervention conducted with an OM, although the difference in average duration often proves to be not statistically significant ( 34 ). Some authors hypothesize that this difference in operative durations can be explained due to a shallower depth of field and constant need for repositioning and refocusing, at least in experimental settings, which might be variable across different brands of exoscopes ( 8 ), while others complain the lack of a mouthpiece ( 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…One of the characteristics ascribed to exoscopes is that they are superior to a conventional OM in terms of ergonomic features both in brain and spine surgery [ 37 , 39 , 49 , 52 , 67 , 69 , 90 , 91 , 92 , 94 , 95 , 96 , 97 , 111 , 112 , 113 , 114 , 115 ], as the ergonomic handling and the ease of intraoperative positioning of the device were found to be beneficial. Second, 3D monitors lead to an improved involvement of the co-surgeon and the scrub nurse during the procedure, and although some authors were satisfied with the high-resolution 3D digital images during surgery [ 52 , 60 , 68 , 73 ], others were not satisfied with the visual quality. In spine surgery, when two neurosurgeons are operating facing each other, the use of 2 monitors each positioned in front of each surgeon allows extreme freedom of movement and modification of the surgical corridor [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rotermund et al [ 95 ] reported the largest series of patients underwent transsphenoidal surgery for pituitary adenoma (239 patients), reporting that no serious episodes or minor complications occurred based on the usage of the exoscope, as well as no significant differences regarding the duration of surgery, complications or extent of resection compared to conventional microscopy. Chen et al [ 73 ] reported a total of 81 patients received tumor resection through the retrosigmoid approach with either an exoscope (39 patients) or an OM (42 patients). Patients in the two groups had comparable tumor location ( p = 0.439) and Koos grading ( p = 0.867).…”
Section: Discussionmentioning
confidence: 99%